Entrepreneurship and Higher Education: An Analysis in Moroccan Universities - Touhami Naoual, Ouazzani (International Journal of Engineering and Technology, 2019)
Although the Moroccan university has become aware of the importance of teaching entrepreneurship and has integrated it in the different university pedagogical curricula, it has, on the other hand, marginalized the support, supervision and accompaniment of students interested in an entrepreneurial career. The teaching of entrepreneurship at the university is certainly a pedagogical instrument, but it should also be a tool for promoting the principles of developing entrepreneurship in students, particularly creativity, innovation, risk taking, self-confidence, autonomy and seizing the opportunity. This article proposes to examine the scope of university entrepreneurship in the Moroccan context through an evaluation of the reality and the status of the diffusion of entrepreneurial culture in students.Â Â Â